Nurses' Views on Using Pasteurized Donor Human Milk for Hypoglycemic Term Infants. Issue 3 (May 2019) - Ferrarello, Debi; Froh, Elizabeth B.; Hinson, Tyonne D.; Spatz, Diane L.
Abstract: Purpose: The purpose of this study was to explore maternal child nurses' knowledge and beliefs about using pasteurized donor human milk (PDHM) to treat newborns with hypoglycemia. Pasteurized donor human milk has been used for decades in neonatal intensive care units, but its use is relatively new in the well-baby population. Study Design and Methods: Focus groups of maternal child nurses were conducted to explore this topic. Results: Six focus groups that included a total 20 nurses were held. Four themes were identified: 1) nurses presumed safety of PDHM but lacked knowledge, 2) nurses' role as patient–family advocate, 3) nurses' logistical concerns about implementation of PDHM, and 4) nurses lacked clarity on formal milk sharing versus PDHM. Clinical Implications: As the use of PDHM increases for well babies, nurses will need more education about PDHM, its safety profile, its use in breastfeeding support and protection of the infant microbiome, and how PDHM differs from informal milk sharing. Nurses play an important role in helping parents weigh risks and benefits of using PDHM or formula when supplementation is needed during the hospital stay. It is important that nurses feel confident in their own knowledge and ability to address parental concerns so they can advocate for their patients and support parental decision-making. Abstract : Pasteurized donor human milk has been used for babies in the neonatal intensive care units for many years but has not been considered an option for treating otherwise healthy term newborns with hypoglycemia. In this study, focus groups of nurses were held to get their views on this practice. Their feedback was used to prepare educational resources for nurses and families about use of pasteurized donor human milk for treating healthy term newborn hypoglycemia.